مآلات فتاوى العلامة البوطي في مواجهة الربيع العربي دراسة تحليلية في أحداث الجمهورية العربية السورية - Methaq SadeqMahmud Almuliki; Ahmad Omar Omar Al-Ahdal; Irwan Mohd Subri (Universiti Sultan Azlan Shah, 2024)
Indexed by Scopus